Introduction to the Artificial Literature - Rahahleh, Ahmad; Alhiary , Moath (Dirasat: Human and Social Sciences, 2022)
The study aims to introduce a new literary term which is “The artificial literature”. The study suggests a number of questions which investigate the most prominent transformation witnessed by the digital literature. It also explores the limits reached by the intermingling between technology and its applications in literature. The study scrutinizes the important issues relating to this case and the main challenges and obstacles. It also answers the question of the purpose of such a study enlisting the shortcomings related to it as the antagonists of the concept see the intermingling between literature and technology. The study concludes that “the artificial literature” applications started to pay attention to literature and seek to make electronic applications and intelligent robots which are able to simulate the human literary production in a way that necessitate a literary and technological research of the outcomes of such work.